Gingival mask for conservative management of gingival recession: A case report - Chaudhary, SK; Agrawal, H; Dhakal, R; Yadav, A (Journal of Nepalese Prosthodontic Society, 2021)
Smile is the jewel of the face, which not only enhances the beauty of the person but also influences self-confidence. Dental esthetic is composed of white and pink component. The long-term periodontal disease results in the destruction of the pink component leading to gingival recession in some cases, which results in elongated tooth with black triangle and unesthetic smile. When severe destruction is present in the maxillary anterior region surgical reconstruction is unpredictable. This destruction can be masked with a prosthesis like gingival mask after the control of periodontal disease. This case report describes the use of the gingival mask as a conservative treatment modality for recession, achieving optimum esthetics and patient satisfaction.